(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical characteristics and Doppler ultrasound findings of patients with lower extremity chronic venous disease treated at Duc Giang General Hospital in 2025. Materials and methods: A cross-sectional descriptive study was conducted on all outpatients diagnosed with lower extremity chronic venous disease from April to September 2025. Results: The study included 342 patients, of which females accounted for 76%. The mean age was 67.3 ± 11.2 years for females and 68.3 ± 9.8 years for males; the age group of ≥ 60 years accounted for the highest proportion (78.3%). The most common functional symptoms were leg heaviness (31.9%) and numbness/tingling (29.8%). There were 52.9% of patients presented at the C0 stage according to the CEAP classification. In our study, the great saphenous vein (GSV) was the most vulnerable (63.2%), with a mean dilated arch diameter of 8.6 ± 1.3 mm and a mean reflux time of 2.1s. The diameter of GSV in the group with structural lesions (C1-C3) was significantly greater than in the C0 group. Furthermore, a positive correlation was observed between the degree of below-knee GSV dilation on ultrasound and clinical severity according to the CEAP classification (p < 0.001). Conclusions: The majority of patients in the study cohort presented at an early clinical stage (C0). Ultrasound findings revealed that venous insufficiency was most prevalent in the great saphenous vein system. Lower extremity venous Doppler ultrasound not only facilitates early diagnosis and prevents lesion oversight but also plays a critical role in severity grading and disease prognosis.